A tangle of knots - Graff, Lisa 1981- (Philomel Books, 2013)
"Destiny leads 11-year-old Cady to a peanut butter factory, a family of children searching for their own Talents, and a Talent Thief who will alter her life forever"--Provided by publisher. Includes cake recipes.